Desafios e oportunidades de carreira na maturidade: um estudo com profissionais brasileiros - Almeida, Edgard Pitta de (2015)
This research addresses issues related to the aging of the Brazilian workforce and intends to investigate the challenges and career opportunities at maturity. For this, we carried out a bibliometric analysis on this topic in the Anglo-Saxon organizational literature and a quantitative-descriptive research based on data collected through an online questionnaire answered by 268 Brazilian professionals with over 35 years of age. Although the sample used does not allow to generalize the results to the population under study, the data demonstrated the aging impacts on the occupation, notably employment; career satisfaction and plans of older workers; and age stereotypes and professional discrimination related to age (ageism). The study aims to contribute to the advancement of the discussions on the Brazilian population aging and its implications for professionals and organizations